Effect of a multidisciplinary supportive program for family caregivers of patients with heart failure on caregiver burden, quality of life, and depression: A randomized controlled study. (October 2016) - Hu, Xiaolin; Dolansky, Mary A.; Su, Yonglin; Hu, Xiuying; Qu, Moying; Zhou, Lingjuan
Abstract: Background: Caregivers of patients with heart failure experience burden and negative health outcomes. Adequate support for family caregivers improves their well-being and the quality of care provided to the patients. However, little is known about the benefits of interventions for caregivers of patients with heart failure in China. Objectives: To test the effects of a multidisciplinary supportive program for family caregivers on caregiver burden, quality of life, and depression. Design: A randomized controlled design with repeated measures was used in this study. Methods: A total of 118 participants were randomized into experimental ( n  = 59) and control groups ( n  = 59) from May to December 2014 in one hospital in Chengdu, People's Republic of China. Participants in the experimental group received a 3-month multidisciplinary supportive program, consisting of three 60-min sessions of group classes, three 30-min peer support groups, and regular telephone follow-ups and consultations, while participants in the control group received usual care only. Outcomes were caregiver burden, quality of life, and depression. Data were collected at baseline, post-test (3 months after discharge), and 3 months after post-test (6 months after discharge). The repeated measures analysis of variance was used to examine the effects of groups, changes over time, and time-group interaction on outcome variables. Results: There were significant improvements in caregiver burden, mental health, and depression after post-test and 3 months after post-test in the experimental group. However, there was no significant improvement in caregivers' physical health at either 3 or 6 months following discharge. Conclusions: A multidisciplinary supportive program for caregivers of heart failure patients had positive effects and provides a unique perspective of an intervention considering Chinese culture and customs.